The artistic value of tombstones of Noratus Cemetery - Baghdasaryan, Satenik (History and Culture, 2025)
A significant aspect of the historical, cultural, and spiritual heritage of the Armenian people finds its roots in the medieval period, with the art of gravestones holding a special place within this rich material culture. Among these, the monuments of the medieval cemetery of Noratus, adorned with sculptures, stand out as integral and essential components. These tombstones serve as invaluable documentary evidence, offering profound insights into the lifestyle, beliefs, perceptions of the afterlife, and traditions of the people.The late medieval sculptures found in Noratus are not only fascinating in terms of their craftsmanship and thematic richness but also serve as a chronicle of life itself which  encapsulate various aspects of everyday life, including production, craftsmanship, occupations, and daily routines. Noratus Cemetery, second in size only to the historical cemetery of Jugha, holds immense significance in both Armenian history and culture. Through extensive fieldwork, a rich comparative material has been amassed, highlighting Noratus's distinction within the Gegharkunik region for its abundant tombstone and khachkar art. This distinction is evident in the diverse themes depicted, the abundance of sculptures, and the chronological range represented. The tombstones of Noratus are not just silent markers of the deceased but vibrant testimonies to the past, preserving the essence of medieval Armenian life and culture for future generations to discover and evaluate․
Keywords: Tombstone art; Noratus; tombstone sculpture; St. Astvatsatsin Church; tombstone of Prince Sahak; cemetery; people of Julfa